Food Waste in the Hospitality and Hotel Industry - Májková, Nikola; Večeřová, Marie; Provazník Ryglová, Kateřina (Marnowanie żywności w branży hotelarskiej, 2025)
This study investigated the issue of food waste in the hospitality sector, with a particular focus on hotels and guesthouses. Its aim was to identify key drivers of food waste generation, evaluate current mitigation strategies, and propose actionable recommendations to support more sustainable food management. A mixed-method approach was employed: first, qualitative interviews with hospitality managers provided in-depth insights into internal practices, followed by a structured questionnaire survey conducted among members of the professional body of hotels and restaurants domain. The findings show that while most establishments reported low levels of food waste (below 10%), systematic monitoring was rare. Buffet-style service emerged as the primary contributor to waste, largely due to guest behaviour. Hospitality professionals highlighted the potential of engaging guests through educational messaging, portion control, and improved planning. A majority of the respondents expressed readiness to adopt new strategies if proven effective. The research also pointed to the importance of training staff and optimising operations to reduce waste. This study explored a research gap with regionally grounded evidence, offering a novel contribution by combining empirical data with practice-oriented solutions applicable to responsible food management in the tourism and hospitality industry. Aim: These authors aimed to identify key drivers of food waste and evaluate existing mitigation strategies in the hospitality sector. It also contributes to broader discussions on sustainability and social responsibility in tourism by offering practical recommendations for more efficient food management.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2025; vol. 69, nr 4, s. 70-78
Keywords: food waste; hospitality industry; sustainable tourism; hotel operations; marnotrawstwo żywności; branża hotelarska; zrównoważona turystyka; działalność hotelarska